Collagenous Colitis-like Condition in Immunosuppressed Infant Baboons (2012)
Collagenous colitis is a chronic inflammatory bowel disease of unknown etiology. It is fairly common in adult humans, but rare in infants, and has been associated with autoimmune disorders. METHODS We report four infant baboons (age 7-12 months) that had received a transplant at 3 months of age and subsequent immunosuppressive therapy for periods of 4-10 months. All presented identical symptoms within a period of 4 weeks, including weight loss associated with chronic watery diarrhea that was unresponsive to standard antimicrobial treatment. RESULTS Clinical chemistry evaluations were within normal ranges, viral causes were ruled out, and fecal and blood cultures were repeatedly negative. At necropsy, two infant baboons were found to have a form of collagenous colitis. In the remaining two baboons that had identical clinical features, immunosuppressive therapy was discontinued and treatment with budesonide was initiated. Both baboons recovered and remained well on no medication until the end of follow-up (24 months).